Effect of Suja (Ginger Milk) Consumption on Sleep Quality in Children with Acute Upper Respiratory Tract Infection - Wati, Ristiani; Antoro, Budi; Anita, Fitri (Inspirasi Foundation, 2026)
Introduction : Upper Respiratory Tract Infection (URTI) in children often causes sleep quality disturbances due to coughing and shortness of breath. Persistent sleep disturbances can inhibit the recovery process and reduce immune function. One nonpharmacological therapy that can be used is the consumption of ginger milk, which has calming and anti - inflammatory effects and may improve sleep quality in children with URTI. Objective: To analyze the effect of suja (ginger milk) consumption on improving sleep quality among children with Upper Respiratory Tract Infection (URTI) in the working area of Kedaton Community Health Center, Bandar Lampung, in 2026. Method: This study employed a quantitative method with a pre-experimental one-group pre-test, post-test design. The research was conducted in the working area of Kedaton Public Health Center, Bandar Lampung City, in 2026, involving 28 children with URTI. Sleep quality was measured before and after the ginger milk intervention using a sleep quality questionnaire, and the data were analyzed bivariately using a paired samples test. Result The results showed that prior to the intervention, most respondents had poor sleep quality, while after ginger milk consumption, an improvement in sleep quality was observed. Bivariate analysis indicated a significant effect of ginger milk consumption on the sleep quality of children with URTI, with a p-value of 0.000 < 0.05. Ginger milk can be used as a complementary nonpharmacological therapy in nursing care for children with URTI. Conclusion: It is recommended that healthcare providers educate parents about the importance of sleep quality in children with URTI and introduce ginger milk as a supportive nonpharmacological therapy.